Developing the OECD 106 fate testing protocol for active pharmaceuticals in soil. Issue 16 (16th July 2021) - Lees, Katherine E.; Fitzsimons, Mark F.; Snape, Jason; Tappin, Alan; Comber, Sean D. W.
ABSTRACT: The ability to determine accurately the fate of APIs in soil is essential for rigorous risk assessment associated with wastewater reuse or biosolid recycling to land, particularly in lower income countries where water and fertiliser is scarce. Four APIs (naproxen, ofloxacin, propranolol and nevirapine) with wide ranging functionality were used as examples in the development of the OECD 106 soil partitioning and/or degradation study, with naproxen used to illustrate applying the full methodology. The data showed key methodological criteria require careful consideration and testing to generate accurate and consistent results. Only glass fibre membranes were suitable for all APIs, without unduly adsorbing APIs to their surface, thus effectively restricting the minimum practical pore size to 0.7 µm. Polypropylene plastic centrifuge tubes were shown to be suitable, with careful determination of recoveries. Direct injection liquid chromatography-mass spectrometry could reliably resolve all 4 APIs down to less than µg L −1 in soil solutions, although allowance for matrix effects via standard additions was required in some cases. Greatest analytical challenges were found for the highest molecular weight API with the greatest affinity for sorption to surfaces (ofloxacin). Key variables that can impact on partitioning such as solution pH and dissolved organic carbon concentrations were shown to vary within tests over time and should be accounted for. GRAPHICAL ABSTRACT: UF0001